2019
DOI: 10.1021/acs.analchem.9b04300
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Differential Scanning Calorimetry by Nonlinear Optical Microscopy

Abstract: Stochastic phase transformations within individual crystalline particles were recorded by integration of second harmonic generation (SHG) imaging with differential scanning calorimetry (DSC). The SHG activity of a crystal is highly sensitive to the specific molecular packing arrangement within a noncentrosymmetric lattice, providing access to information otherwise unavailable by conventional imaging approaches. Consequently, lattice transformations associated with dehydration/desolvation events were readily ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The integration of a SHG microscope with DSC would allow to monitor phase transitions of individual particles and the combination of both instruments was referred to as Stochastic differential scanning calorimetry (SDSC). 80 The authors measured phase transitions of supersaturated solutions of urea and D-(+) trehalose dihydrate for benchmarking the technique. The SHG imaging was sensitive to the packing arrangements of the crystals and this would not be observable with conventional microscopy.…”
Section: Inorganicsmentioning
confidence: 99%
“…The integration of a SHG microscope with DSC would allow to monitor phase transitions of individual particles and the combination of both instruments was referred to as Stochastic differential scanning calorimetry (SDSC). 80 The authors measured phase transitions of supersaturated solutions of urea and D-(+) trehalose dihydrate for benchmarking the technique. The SHG imaging was sensitive to the packing arrangements of the crystals and this would not be observable with conventional microscopy.…”
Section: Inorganicsmentioning
confidence: 99%
“…Wax crystallization is accompanied by heat release, which is detected by the measuring system. Using this method, it is possible to measure with high accuracy the temperature of the phase transition in the studied fluid (Sherman et al 2019;Vicky Kett et al 2016). The method makes it possible to directly measure the enthalpy of wax crystallization.…”
Section: Differential-scanning Calorimetrymentioning
confidence: 99%
“…Pokhrel et al 19 performed XRPD and HR-TEM analysis during in situ heating but separately. Therefore, to our best knowledge XRPD and microscopy have never been coupled during an in situ XRPD experiment in a laboratory setup to obtain DSC-like data, and only Sherman et al 20 reported on a setup developed to detect stochastic phase transitions in single crystalline particles integrating a second harmonic generation microscope with an optical DSC stage. 21 The small number of publications about in situ XRPD studies of crystallization/melting of salt aqueous solutions can be ascribed to the difficult or impossible usage of standard low temperature XRPD setups, typically not suitable to investigate liquid samples because of evaporation, instrumental damage, and the need to use a very limited amount of sample.…”
Section: ■ Introductionmentioning
confidence: 99%